Question #af298

2 Answers
Aug 31, 2017

Function f(x) takes the input value of x, multiplies it by #-6#, and then adds 2.

The inverse function reverses this. Take the input value, subtract 2 from it, then divide by -6

Or, #f^-1 (x)= (x-2)/-6 #.

You should always verify with some example input values.

Say, x = 2: #f(2) = (-6* 2) + 2 = -10#

#f^-1(-10) = (-10 -2)/-6 = (-12)/-6 = 2#

So, you get back the original input value you put in for f(x).

Try it with some additional values to be sure.

#f(3) = -16#, and #f^-1(-16) = (-18)/-6 = 3#, etc.

Try with some negative values:

#f(-3) = 20#, and #f^-1(20) = -3#, and so on.

Aug 31, 2017

#f^-1(x) = -1/6 x + 1/3#.

Explanation:

To find the inverse of #f(x) = -6x +2#, switch the variables #x# and #y# and then solve for #y#.

#y = -6x+2#

#x = -6y + 2# #-># switch the variables

#x - 2 = -6y#

#y = -(x-2)/6#

#y = - 1/6 x + 2/6#

#y = - 1/6 x + 1/3#

So, #f^-1(x) = -1/6 x + 1/3#.

We can verify this by graphing the function and its inverse; #f^-1(x)# should be a reflection of #f(x)# over the line #y=x#.

desmos.com

It's clear to see that #f(x)# (red) and #f^-1(x)# (blue) are reflections of one another over #y=x# (green).